The Moderating Effect of Tax Volunteers on Taxpayer Compliance - Susilawati, Heni; Haryanti, Kurniati Kevin; Puspa, Regita Dwi; Yulianto, Agung (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: With an emphasis on the role of tax volunteers, taxpayer comprehension, tax penalties, awareness, and E-SPT use, this study attempts to investigate the factors impacting MSME taxpayer compliance in Cirebon Region Three. Design/methodology/approach: By gathering primary data from respondents—specifically, MSME taxpayers assisted by tax volunteers at KPP Pratama Region Three Cirebon—The design of this investigation is quantitative. Findings: According to the report, MSME taxpayer compliance is greatly and favorably impacted by understanding of tax, tax sanctions, and taxpayer awareness. By fostering better socialization and education, tax volunteers also increase taxpayer compliance. Research limitations/implications: The study is limited to MSME taxpayers in Cirebon Region Three and may not fully represent other regions or sectors. Practical implications: Strengthening tax volunteer programs and enhancing taxpayer education initiatives are critical to boosting MSME compliance. Originality/value: This research highlights the strategic role of tax volunteers in fostering MSME taxpayer compliance, an area rarely explored in previous studies. Paper type: a Research Paper